Preoperative inflammatory biomarkers reveal renal involvement in postsurgical mortality in hip fracture patients: an exploratory study - Valdes, Ana M.; Ikram, Adeel; Taylor, Lauren A.; Zheng, Amy; Kouraki, Afroditi; Kelly, Anthony; Ashraf, Waheed; Vijay, Amrita; Miller, Suzanne; Nightingale, Jessica; Selby, Nicholas M.; Ollivere, Benjamin J. (Frontiers in Immunology, 2024)
Background Hip fractures in frail patients result in excess mortality not accounted for by age or comorbidities. The mechanisms behind the high risk of mortality remain undetermined but are hypothesized to be related to the inflammatory status of frail patients. Methods In a prospective observational exploratory cohort study of hospitalized frail hip fracture patients, 92 inflammatory markers were tested in pre-operative serum samples and markers were tested against 6-month survival post-hip fracture surgery and incidence of acute kidney injury (AKI). After correcting for multiple testing, adjustments for comorbidities and demographics were performed on the statistically significant markers. Results Of the 92 markers tested, circulating levels of fibroblast growth factor 23 (FGF-23) and interleukin-15 receptor alpha (IL15RA), both involved in renal disease, were significantly correlated with 6-month mortality (27.5% overall) after correcting for multiple testing. The incidence of postoperative AKI (25.4%) was strongly associated with 6-month mortality, odds ratio = 10.57; 95% CI [2.76–40.51], and with both markers plus estimated glomerular filtration rate (eGFR)– cystatin C (CYSC) but not eGFR-CRE. The effect of these markers on mortality was significantly mediated by their effect on postoperative AKI. Conclusion High postoperative mortality in frail hip fracture patients is highly correlated with preoperative biomarkers of renal function in this pilot study. The effect of preoperative circulating levels of FGF-23, IL15RA, and eGFR-CYSC on 6-month mortality is in part mediated by their effect on postoperative AKI. Creatinine-derived preoperative renal function measures were very poorly correlated with postoperative outcomes in this group.